Optimal water pump scheduling in an open reservoir water treatment system, incorporating evaporation and seepage effect - Patrick, Ngancha Bonja (Central University of Technology, 2022)
Bulk water extraction and purification, in most countries, occurs in distant areas, where running rivers or lakes are available. To achieve the goal of obtaining potable water, water from dams or lakes is pumped into a treatment reservoir, to undergo purifying operations. Electrical energy is required for the supply of these electric pumps, to pump water from one level to another, during the process. Looking at the energy management point of view, the main problem is the rising cost of electrical energy used to pump water from the dam to the reservoirs. This could be owing to inadequate management of the pumping system, as well as the fact that water reservoir pumping systems are subject to exogenous variables, including evaporation, precipitation, seepage and leakage. A review of water-pump energy management steps in a bulk-water purification system, was conducted, to understand the problem and find the best possible solution in enhancing the energy usage in a water pumping system. This survey provides a complete overview of current control strategies in water pumping energy management activities. The review is led by the performance, operation, equipment and technology (POET) concept, which includes a review of current water pumping technologies, as well as advancements, ideas, evaluations and improvements. This POET framework discussed the long term viability of a broad energy management program, as an application of the commercial bulk water development scenario. The case study established that the POET based energy management system may save energy in a coordinated and effective manner. It may be able to successfully obtain the energy saving prospects of water pumping processes, as well as laying the groundwork for a future project in water treatment systems. This research proposes different energy management models, to meet the pumping water demand while minimizing the amount of energy required during the operation. The first model was based on the mathematical model for water pumping controller systems and is known as the research's baseline model. The system takes into consideration the impacts of evaporation, rainfall and seepage to make the model more realistic and it uses the flood switching principle, regulating the pumping operation of a water facility. To assess the initial model's performance, simulations were run in two scenarios: first, evaluating the flood switching control system without taking into account the effects of rainfall, evaporation, and seepage, and second, with all of these constraints taken into account. The second model was based on the principle of timer-setting control. When the effects of evaporation, rainfall, and seepage losses were all considered, the performance of the suggested electrical timer switching control system was evaluated. The simulation of the second model was carried out using two scenarios: first, a time control system was applied to a fixed water pump, and second, a timer-setting control system was incorporated with the VFD power control pump. The optimal switching control system was used in the third model. Evaporation, rainfall, and seepage losses were all elements taken into account in order to make the model more realistic. The simulation of the third model was divided into two categories: first, an optimal control system was applied to a fixed water pump, and second, the optimal control system combined with the VFD power control pump. The main objective of this research was to optimise the pumping operation of a water pumping system, with the aim of obtaining a lower energy consumption cost. MATLABSCIP optimization software was used to implement the developed models. Hence, the model's energy-saving capabilities were validated through simulation. In comparison to the baseline case, in which the developed model is simulated with the impacts of evaporation, rainfall and seepage; and then again without these disturbances, the results of the first model show an energy savings of 683ZAR per day, when the effect of evaporation, seepage and rainfall are all taken into consideration in a flood switching control system. The simulated results of the second model are compared to the baseline flood switching control system, to estimate the economic benefit of the developed model. As compared to the baseline case, where the flood switching control system is used to accommodate the load demand, the simulated results for the selected day of operation have shown that, using the proposed timer-setting control model with fixed speed motor pump, a 316 ZAR reduction in the operating cost is achieved, compared to the baseline flood switching control system. Looking further, when a VFD control motor pump is added to the timer-setting control system, the simulated result shows that a 1022 ZAR decrease in operating cost per day may be saved, when compared to the baseline flood switching control system. In a separate simulation of the third model, the results are compared to the baseline flood switching control system, to estimate the economic benefit of the developed model. When the optimal control system is employed to meet the load requirement, the simulated results for the chosen day of operation demonstrate that, when compared to the baseline flood switching control system, the proposed optimal control model with fixed speed motor pump, saves 1204 ZAR in operating costs. When a VFD control motor pump is introduced to the optimal control system, the simulated result shows that, when compared to the baseline flood switching control system, a 1725 ZAR reduction in operating cost per day may be achieved. These findings further revealed that the grid's energy demands are significantly reduced when the proposed optimal control models are combined with a VFD control motor pump in a water pumping system. As a result, the initial cost of acquiring energy is reduced. Further services, such as maintenance, could benefit from the savings. In the end, this may assist in lowering the initial cost of water sold to consumers.
Thesis (Doctor :Engineering: Electrical Engineering)--Central University of Technology
Keywords: Water pumping; Optimal water pumping; Water pump energy management; Bulk-water purification; POET framework